Improving Public Services in Realizing Good Governance in Indonesia - Rahmat Salam (Global Writing Academica Researching & Publishing, 2023)
Public service is one of the obligations that must be carried out by the government towards its people. The success of public services will produce good governance. However, at the same time, bad public servants can hinder the realization of good governance. This research then aims to look at how good public services can help realize the formation of good governance. This research will be carried out using a qualitative approach and a literature study method. The research data comes from the results of previous studies. The results of this study then found that one of the essences of good governance is good public service. This is because good public services show good government management performance. There are various factors to be able to improve the quality of public services, such as the transparency of public service management costs, the formation of one-stop public services (one-stop services), to the reform of employees in public services.